Predictors of the response to phosphodiesterase-5 inhibitors in pulmonary arterial hypertension: an analysis of the Spanish registry - Agustin R. Garcia; Isabel Blanco; Lluis Ramon; Jesús Pérez-Sagredo; Francisco J. Guerra-Ramos; Clara Martín-Ontiyuelo; Olga Tura-Ceide; Francisco Pastor-Pérez; Pilar Escribano-Subías; Joan A. Barberà (Respiratory Research, 2023)
Abstract Background Achieving and maintaining a low-risk profile is associated with favorable outcome in pulmonary arterial hypertension (PAH). The effects of treatment on risk profile are variable among patients. Objective To Identify variables that might predict the response to treatment with phosphodiesterase-5 inhibitors (PDE-5i) in PAH. Methods We carried out a cohort analysis of the Spanish PAH registry in 830 patients diagnosed with PAH that started PDE5i treatment and had > 1 year follow-up. 644 patients started PDE-5i either in mono- or add-on therapy and 186 started combined treatment with PDE-5i and endothelin receptor antagonist (ERA). Responders were considered when at 1 year they: (1) were alive; (2) did not present clinical worsening; and (3) improved European Society of Cardiology/European Respiratory Society (ESC/ERS) risk score or remained in low-risk. Univariate and multivariate logistic regression models were used to analyze variables associated with a favorable response. Results Two hundred and ten patients (33%) starting PDE-5i alone were classified as responders, irrespective of whether it was mono- or add-on therapy. In addition to known predictors of PAH outcome (low-risk at baseline, younger age), male sex and diagnosis of portopulmonary hypertension (PoPH) or HIV-PAH were independent predictors of favorable response to PDE-5i. Diffusing capacity for carbon monoxide (DLco) ≤ 40% of predicted was associated with an unfavorable response. When PDE-5i were used in upfront combination, 58% of patients were responders. In this group, diagnosis of idiopathic PAH (IPAH) was an independent predictor of favorable response, whereas connective tissue disease-PAH was associated with an unfavorable response. Conclusion Male sex and diagnosis of PoPH or HIV-PAH are predictors of favorable effect of PDE-5i on risk profile when used as mono- or add-on therapy. Patients with IPAH respond more favorably to PDE-5i when used in upfront combination. These results identify patient profiles that may respond favorably to PDE-5i in monotherapy and those who might benefit from alternative treatment strategies.